2019
DOI: 10.1186/s13023-019-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and autonomic function in patients with Wilson’s disease

Abstract: BackgroundThe clinical effect of copper accumulation on the heart of patients suffering from Wilson’s disease (WD) is not completely understood. We aimed to determine if patients with WD show signs of cardiac involvement, structural heart disease or autonomic dysfunction. In this prospective trial, we studied 61 patients (mean age 44.3 ± 15.2 years, 51% males) with WD and compared them to 61 age- and gender-matched healthy controls. All subjects underwent clinical examination, blood tests, echocardiography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
0
24
0
3
Order By: Relevance
“…However, structural changes are rarely seen in the usually stable WD patients under medical treatment, when transferred to standard cardiac examination [ 4 ]. As presented previously, asymptomatic WD patients had grossly normal systolic left heart (ejection fraction, end diastolic diameter) and right heart function (end diastolic diameter, tricuspid annular plane systolic excursion, right ventricular systolic pressure) in echocardiography; only mild diastolic dysfunction was present compared to healthy controls [ 9 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, structural changes are rarely seen in the usually stable WD patients under medical treatment, when transferred to standard cardiac examination [ 4 ]. As presented previously, asymptomatic WD patients had grossly normal systolic left heart (ejection fraction, end diastolic diameter) and right heart function (end diastolic diameter, tricuspid annular plane systolic excursion, right ventricular systolic pressure) in echocardiography; only mild diastolic dysfunction was present compared to healthy controls [ 9 ].…”
Section: Discussionmentioning
confidence: 90%
“…Patients were part of the CARMA Wilson’s disease study (Cardiac manifestation of Wilson’s disease). Conventional CMR data, echocardiography and autonomic function data were published elsewhere [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cases of cardiac sudden death and an increased incidence of arrhythmias and heart failure have been reported. Just recently, we have demonstrated that even asymptomatic patients exhibit structural disease and autonomic dysfunction of the heart [1, 2].…”
mentioning
confidence: 99%
“…Elkiran et al studied 22 children with Wilson's disease, and theyreported diastolic dysfunction[18]. In another study, the LV systolic function measured by ejection fraction did not differ significantly between Wilson's disease and controls, however, diastolic dysfunction was more frequent in patients with Wilson's disease[19].Hlubocka Z et al compared 2D echocardiographic data of 42 patients withWilson's disease to 42 healthy subjects. They reported a non-significant trend towards lower LV ejection fraction values in patients with Wilson's disease (62% versus 64%), the LV diastolic function did not differ in the two groups[20].In a recent study by Quick et al, 61 patients with Wilson's disease were evaluated by cardiac magnetic resonance.…”
mentioning
confidence: 99%